Micaela Bastidas: apuntes on her role conflicto - Kanashiro , Amparo (Revista revoluciones, 2021)
In the framework of the commemoration of the Bicentennial of the Independence of Peru, the article aims to contextualize the roles played by Micaela Bastidas, through a compilation of letters written by the notaries of Micaela Bastidas, who reflected their ideas and requests in a written, in the midst of the rebellion between 1780 and 1781. Likewise, part of his responses to the interrogation of the criminal process to which he was subjected for his participation in the rebel movement is examined. This context takes us to a historical empathy with Micaela, since she had to deal between her role as mother and heroine from a gender perspective. Most of the letters correspond to the efforts that Micaela made multiplying her roles, as well as the efforts and commitments made by her husband, children and the rest of her family to defeat the royalist troops. Micaela broke the scheme of a passive subject and relegated to the private space to be the protagonist of the public space despite the conflict of roles that she assumed.